Vaccination of Holstein heifers with Mycobacterium bovis BCG strain induces protection against bovine tuberculosis and higher milk production yields in a natural transmission setting. Issue 3 (22nd May 2021) - Retamal, Patricio; Ábalos, Pedro; Alegría‐Morán, Raúl; Valdivieso, Nicolás; Vordermeier, Martin; Jones, Gareth; Saadi, Karina; Perez Watt, Carolina; Salinas, Constanza; Ávila, Constanza; Padilla, Valentina; Benavides, Belén; et al.
Abstract: Bovine tuberculosis (TB) is a chronic disease caused mainly by Mycobacterium bovis, a zoonotic pathogen that has a worldwide distribution causing serious economic losses for milk and meat producers. In Chile, the disease in dairy cattle has a heterogeneous distribution, where the Metropolitan Region concentrates the highest animal prevalence and the main challenge for the national control and eradication programme. In this epidemiological context, vaccination with the M. bovis Bacillus Calmette–Guerin (BCG) vaccine might be a useful strategy for disease prevention and control. The objective of this study was to assess the efficacy and impacts on productivity and fertility of vaccination with the BCG Russia strain in 11 month‐old heifers from a dairy farm, under a natural transmission condition. Sixty‐two animals were vaccinated via the subcutaneous route with the equivalent of one human dose of BCG, and 60 control animals received saline. Subsequently, blood sampling was performed at 3, 6, 9, 12, 15 and 18 months post‐inoculation, and infection status was determined using the IFNγ release assay (IGRA) with the DIVA (differentiate infected from vaccinated animals) antigens ESAT‐6, CFP‐10 and Rv3615c. Efficacy was calculated as the percentage of reduction in the incidence of infection attributable to vaccination, which showed a statistically significant level of overall protection of 66.5%. No adverse effects on fertility and production were recorded. In contrast, we observed beneficial effects of vaccination on several milk production parameters, with the milk yield in the first 100 days after calving in the BCG group significantly higher compared to unvaccinated heifers ( p  < .05). These results suggest that BCG vaccination of heifers in a natural transmission setting might result in both sanitary and productive benefits, supporting its implementation as a new strategy for TB prevention in a high prevalence area of Chile.